Transformational Leadership of Madrasah Principals in Instilling Religious Values in State Madrasah Aliyah Jambi Province - Susrianto, Doni; Syukri, Ahmad; Us, Kasful Anwar (Journal of Social Work and Science Education, 2024)
Because of idealistic behavior, motivation encourages subordinates to be creative and innovative, and is very understanding and appreciative of subordinates, Transformational leadership of madrasa heads should have a positive effect in instilling religious values, but why is transformational leadership of madrasa heads not optimal in instilling religious values in MAN Jambi Province. The goal of this study was to determine the success of the madrasa head’s transformational leadership in instilling religious values in MAN Jambi Province. The qualitative method was used in this study. Data collection methods include observation, interviews, and documentation. Data was analyzed by collecting data, reducing data, presenting data, and finally verifying data. The findings of this study are as follows: 1) the transformational leadership of the madrasah head in instilling religious values in MAN Jambi Province is too tolerant of subordinates’ inability; 2) has not been able to do it persuasively; and 3) has not been able to improve skills continuously. 4). Not yet capable of converting potential into actual energy. The transformational leadership of the head of the madrasah aliyah Jambi Province has not been optimal in instilling religious values in MAN Jambi Province, according to the research findings.